Evaluation of the Morphology and Malachite Green Absorption Capacity of Modified Electrospun Chitosan Nanofibers - Nguyen, Hien Thi Thanh; Dang, Thao Thi Ngoc; Ha, Tan Minh; Nguyen, Nhi Tran Yen (Universitas Gadjah Mada, 2025)
This article studies the factors affecting the morphology of electrospun chitosan nanofibers modified with polyvinyl alcohol (PVA) and using formed nanofibers for malachite green (MG) adsorption. Chitosan concentrations of 2 and 3 wt.% combined with PVA, the nanofibers are formed with sizes under 75 nm, in contrast to the results of the chitosan solutions formed particles. This result is due to the interaction between the functional group of the polymers that increases entanglement. Machine operating and polymer solution parameters affect the nanofiber morphology. Combining the principal component analysis (PCA) method and physicochemical analysis showed that the factors of chitosan solution, such as concentration, viscosity, and conductivity, mainly influenced the fiber formation process. Besides, the initial test results of CTS 3 wt.%/PVA (1:1) nanofibers adsorbing MG at 10 mg/L concentration exhibited a high adsorption performance (more than 89%), and the amount of absorbed dye (35.83 mg/g) after 120 min at pH 6.8. The obtained results will be worth information for creating chitosan nanofibers by electrospinning the next time and evaluating the MG adsorption capacity of chitosan nanofibers in the presence of PVA.